Experimental Study of Natural Convection Heat Transfer in Confined Porous Media Heated From Side (Journal of Engineering, 2013)
Transient three-dimensional natural convection heat transfer due to the influences of heating from one side of an enclosure filled with a saturated porous media, whereas the opposite side is maintained at a constant cold temperature, and the other four sides are adiabatic, were investigated in the present work experimentally. Silica sand was used as a porous media saturated with distilled water filled in a cubic enclosure heated from the side,using six electrical controlled heaters, at constant temperatures of (60, 70, 80, 90, and 100oC). The inverse side cooled at a constant temperature of (24oC) using an aluminum heat exchanger, consisted of 15 channels feeded with constant temperature water. Eighty thermocouples were used to control the heated and cooled sides, and to measure the temperature in the entire enclosure. Experimental results showed that the heat transfer regime was mainly conduction for all Rayleigh numbers with small influence of convection for Ra=42 and greater for Ra=55. This effect increased with the angle of inclination of the enclosure. Numerical and experimental results showed a good agreement. There was a rapid increase in the temperature at the entire media at the early time, reduced gradually until the steady state condition reached. This temperature and heat transfer to and from the porous media, were increased as the Rayleigh number and/or inclination angle increased. The Nusselt number increased directly with the angle of inclination up to o θ = 45 and then decreased. Correlation equations are obtained from the experimental investigation, showed the change of the average and local Nusselt number with time, distance, Rayleigh number, and the inclination angle.